To Study the Worthiness in Fixed Deposit (FD) Investment in Malaysia - Dr Yeoh Wee Win (Open Academia, 2023)
The purpose of the study is targeted to study the worthiness in fixed deposit (FD) investment in Malaysia. The main objective of investment is to grow the wealth of the investment value to surpass the rising inflation in the economy of Malaysia. There is multiple suggestion provide the impression that the FD investment is not likely to yield sufficient return to cover the inflation rate in the country. Therefore, this has motivated the research to investigate the performance of the FD investment in Malaysia. The quantitative analysis had been conducted with the development of the study through the period of 1966 to 2022 to explore the relationship between the inflation rate and the FD investment return as the comparative analysis to demonstrate the performance of the FD investment. As a result, the inflation rate had identified the significant positive impact towards the movement of the FD rate of return suggesting the similar growth direction for both the FD investment and the inflation rate of the local economy. The comparative analysis had proven that the FD investment had yield higher returns to overcome the rising inflation pressure for the Malaysian investors. With this, the outcome of the study had drawn the suggestion and recommendation to invest in FD as an investment strategy to offset the impact rising inflation in Malaysia.
Keywords: fixed deposit; Malaysia; fixed depositinflation